Mobile Learning via SMS at Open University Malaysia: Equitable, Effective, and Sustainable - Lim, Tina; Fadzil, Mansor; Mansor, Norziati (International Review of Research in Open and Distributed Learning, 2011)
This article describes Open University Malaysia’s efforts at enhancing the blended learning approach for undergraduate distance learners with the successful implementation of the Mobile Learning via SMS initiative. The pilot project was implemented in the May 2009 semester, and this coming January 2011 semester will be in its sixth consecutive semester. Aspects such as the conceptual model, the process flow of group messaging, and challenges faced, as well as effectiveness of the initiative, are discussed.